2016
DOI: 10.3892/mmr.2016.5039
|View full text |Cite
|
Sign up to set email alerts
|

p38 mitogen-activated protein kinase inhibition modulates nucleus pulposus cell apoptosis in spontaneous resorption of herniated intervertebral discs: An experimental study in rats

Abstract: Abstract. The present study was performed to investigate the role of p38 mitogen-activated protein kinase (MAPK) in the resorption of herniated intervertebral discs in 30 rats. In the non-contained and p38 MAPK inhibition (p38i) groups, two coccygeal intervertebral discs (IVDs) were removed and wounded prior to relocation into the subcutaneous space of the skin of the back. In the contained group, the cartilage endplates maintained their integrity. Furthermore, SB203580 was injected intraperitoneally into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Importantly, activation of p38 and ERK in our canine samples may not only induce downstream expression of additional inflammatory mediators and matrix degrading enzymes and hence play an important role in disease progression [reviewed in Ref. ( 27 )], but may furthermore be a means to initiate resorption of non-contained herniated disc tissue ( 102 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, activation of p38 and ERK in our canine samples may not only induce downstream expression of additional inflammatory mediators and matrix degrading enzymes and hence play an important role in disease progression [reviewed in Ref. ( 27 )], but may furthermore be a means to initiate resorption of non-contained herniated disc tissue ( 102 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…97 Mitogen activated protein kinase (MAPK) and Ras pathways are involved in the development and persistence of radicular pain and motor dysfunction by modulating the activities of pro-inflammatory, autophagic, and apoptotic cytokines and regulators, and targeting them can alleviate such pathological responses and further induce resorption of IVDs. [146][147][148][149][150][151][152] The repression of the mammalian target of rapamycin (mTOR) pathway can attenuate IDH-induced pain and radiculopathies. 153 The activity of the neurotrophin pathway is related to inflammatory IVD degeneration and its associated pain responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat LDH model, our group observed that when the herniated IVD was ruptured or dissociated, the rate of apoptosis was higher than that of the unruptured and normal IVD [ 131 ]. Among the cytokines released by macrophage infiltration, some cytokines, such as Fas, IL-2, and HIF-α, have been shown to induce apoptosis of intervertebral disc nucleus pulposus cells, thereby promoting LDH reabsorption [ 132 134 ].…”
Section: The Mechanism Of Ldh Reabsorptionmentioning
confidence: 99%
“…Wang et al [ 135 ] found that IL-2 induces apoptosis in NP cells and activates the p38 MAPK signaling pathway. Activated p38MAPK signaling pathway induces apoptosis in NP cells and accelerates the reabsorption of ruptured LDH [ 131 ].…”
Section: The Mechanism Of Ldh Reabsorptionmentioning
confidence: 99%